Planning, Implementing and Evaluating Capacity Development - Horton, Douglas (International Service for National Agricultural Research, 2002)
This paper discusses 10 basic issues involved in planning, implementing, and evaluating capacity-development efforts in research and development organizations. Capacity development is the process by which individuals, groups, and organizations improve their ability to perform their functions and achieve the desired results over time. Without capacity development in research and development organizations in the South, the gap between the rich and the poor will continue to grow. Organizational capacity development can be an important vehicle for improving an organization's performance. Capacity-development efforts should be planned so that they improve those capacities that most severely hamper performance levels.